We have tailored Africa - (:unkn) unknown (My University, 2011)
After the First World War, the discourse and methods used to determine and define boundaries changed radically. In Europe, the territorial agreements of 1919-20 put forward an ideal of territorial homogeneity, a concept based on the ideal correspondence of state, nation and territory. Meanwhile, in Africa, the French colonizers were also reconsidering their spatial arrangements along the same lines. In this context, the expertise of the social sciences became crucial in defining territory and therefore in political decision-making. At the same time, prominent representatives of the new colonial sciences were responsible for developing and disseminating the idea of the 'artificiality' of African boundaries. This new generation of experts on French colonization considered the borders of Africa to be scars left behind by the old and arbitrary colonial order, which they wished to see replaced by a more humanistic rule. Their discourses, however, offered a vision of Africa based on the continent's exceptional character. In essence, Africa was considered as a continent defined principally along ethnic territorial lines, a logic excluding any political definition of territory. This discourse contributed to redefining the continent as something radically other.
Keywords: African Research